2015
DOI: 10.5194/acp-15-5557-2015
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-biennial oscillation of the tropical stratospheric aerosol layer

Abstract: Abstract. This study describes how aerosol in an aerosolcoupled climate model of the middle atmosphere is influenced by the quasi-biennial oscillation (QBO) during times when the stratosphere is largely unperturbed by volcanic material. In accordance with satellite observations, the vertical extent of the stratospheric aerosol layer in the tropics is modulated by the QBO by up to 6 km, or ∼ 35 % of its mean vertical extent between 100-7 hPa (about 16-33 km). Its largest vertical extent lags behind the occurren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 77 publications
(138 reference statements)
5
34
0
Order By: Relevance
“…6) a volcanic signature is hardly apparent in the latitudinally resolved time series and the main variability component at low latitudes has a period characteristic of the Quasi-Biennial Oscillation (QBO, reviewed by Baldwin et al, 2001). The enhanced tropical aerosol extinction values at 30 km altitude occur during easterly shear conditions of the QBO (Trepte and Hitchman, 1992;Hommel et al, 2015). The bottom right panel of Fig.…”
Section: Sample Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6) a volcanic signature is hardly apparent in the latitudinally resolved time series and the main variability component at low latitudes has a period characteristic of the Quasi-Biennial Oscillation (QBO, reviewed by Baldwin et al, 2001). The enhanced tropical aerosol extinction values at 30 km altitude occur during easterly shear conditions of the QBO (Trepte and Hitchman, 1992;Hommel et al, 2015). The bottom right panel of Fig.…”
Section: Sample Resultsmentioning
confidence: 99%
“…The results demonstrate that enhancements in aerosol extinction at 30 km altitude are linked to strong easterlies at the 10 hPa pressure level. These enhancements in aerosol extinction are caused by an upward motion, which is a manifestation of the QBO secondary oscillation induced by meridional temperature gradients caused by the wave-driven vertical wind shear (Trepte and Hitchman, 1992;Baldwin et al, 2001;Hommel et al, 2015). Brinkhoff et al (2015) recently discussed the underlying physical mechanisms, also based on SCIAMACHY stratospheric aerosol measurements, in more detail.…”
Section: Sample Resultsmentioning
confidence: 99%
“…Based on satellite observations, Trepte and Hitchman (1992) have shown that transport from the tropics to the midlatitudes is favored during westerly shear phases of the quasi-biennial oscillation (QBO) rather than during the easterly shear phases. More recently, through the use of satellite observations and climate models, Hommel et al (2015) revealed that the vertical and latitudinal extent of the stratospheric aerosol layer (between 16 and 31 km) in the tropics is modulated by the QBO. Pitari et al (2016b) analyzed the radiative perturbations in the stratosphere induced by the last five major volcanic eruptions after 1960 (i.e, Agung, Mount St. Helens, El Chichón, Nevado del Ruiz, and Pinatubo) using a climate model that included an aerosol microphysics module for aerosol formation and growth.…”
mentioning
confidence: 99%
“…On the other hand, the modulation the QBO itself may introduce on the stratospheric aerosol lifetime (and deposition) has not been explored in 5 depth in case of a geoengineering constant tropical injection of sulfur. This effect, however, was studied for the time evolution of the unperturbed stratospheric aerosol layer by Hommel et al (2015). They found that the aerosol burden non-linearly correlate with the QBO phase because of a wide range of reasons, amongst those the rather wide differences in the size range of the aerosols.…”
Section: Qbo Impact On Stratospheric Sulfatementioning
confidence: 99%